A prestressed anchor-grouting reinforcement method based on the novel HFQSME grouting material for deep high-stress fractured rock mass - Junhao Xu; Jinpeng Zhang; Beibei Li; Xuefeng Liu; Kesheng Li; Chuanxiao Liu (Case Studies in Construction Materials, 2024)
In order to control the surrounding rock of deep high-stress roadways, a new prestressed anchor-grouting reinforcement method was proposed with an engineering background of the 1780 ventilation roadway of Shiyakou Coal Mine. A high-fluidity quick-setting micro-expansion (HFQSME) grouting material had been developed through superplasticizer, accelerator, and expansion agent. The results showed that the optimal ratio of HFQSME grouting material was superfine Portland cement of 95 %, superplasticizer of 0.5 %, accelerator agent of 0.5 %, expansion agent of 5.0 %, and water-binder ratio of 0.4. The fluidity, initial setting time and expansion rate of the grouting material were 47 cm, 41 minutes and 0.12 %, respectively. The grouting reinforcement effect of superfine slurry and HFQSME grouting material on rock mass with different degrees of fragmentation was investigated. The peak strength of rock mass with two degrees of fragmentation reinforced by HFQSME grouting material was 166 % and 233 % higher than that of superfine slurry. The macro reinforcement effect of HFQSME grouting material on the surrounding rock of deep high-stress roadway was evaluated through industrial testing. The prestressed anchor grouting method was used to improve the original support design scheme, and data monitoring and analysis were conducted on site. Compared with the original supporting scheme, the deformation of the 1780 ventilation was significantly reduced. Therefore, HFQSME grouting material had good adaptability for the surrounding rock of deep high-stress roadways.